2012
DOI: 10.1177/1464884911431536
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interventionist regulation in reshaping news agendas: A comparative analysis of public and commercially funded television journalism

Abstract: In this article we draw on a specific case study -the re-regulation of BBC political reporting in the nations and regions in the UK post-devolution -to compare the BBC's interventionist, public service framework with the 'light touch' regime of commercial broadcasting. We carried out a content analysis of BBC Television News (where issues of accuracy and impartiality are regulated by the BBC Trust), and three commercially funded channels (where programme content is entirely regulated by Ofcom) before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…While impartiality is a normative aim for many broadcast journalists, scholars have long studied how it can be measured empirically in news coverage-exploring, for example, the type of news agenda pursued by different broadcasters, the sources used in coverage or the degree of contextual information about a particular issue or event (Barkho 2014;Cushion, Lewis, and Ramsay 2012;Wahl-Jorgensen et al 2016 To what extent are statistical claims accepted or challenged?…”
Section: Introductionmentioning
confidence: 99%
“…While impartiality is a normative aim for many broadcast journalists, scholars have long studied how it can be measured empirically in news coverage-exploring, for example, the type of news agenda pursued by different broadcasters, the sources used in coverage or the degree of contextual information about a particular issue or event (Barkho 2014;Cushion, Lewis, and Ramsay 2012;Wahl-Jorgensen et al 2016 To what extent are statistical claims accepted or challenged?…”
Section: Introductionmentioning
confidence: 99%
“…But there has been less sustained academic engagement with how different political systems influence the information environment and affect the opportunities to learn about politics. Although comparative studies have theorised how political dimensions can help shape national media systems (Cook, 1998), few empirical news studies focus on the complexities of understanding power and responsibility, especially in the many countries where that power is devolved and dispersed between local, regional and national governments (Cushion, 2012;Cushion et al, 2009Cushion et al, , 2012Dekavalla, 2012). This is particularly important when power is not only devolved to different levels of government, but where those levels can be politically distinct.…”
Section: Content Analysis Democracy Interviews Politics/political mentioning
confidence: 99%
“…While the UK government still holds reserved powers, in areas like immigration or defence, the devolved institutions now have considerable policy-making power. Previous research about how devolution is reported in the United Kingdom has shown the media have largely ignored politics outside England and struggled to accurately reflect policy debates in Scotland, Wales and Northern Ireland (Cushion, 2012;Cushion et al, 2009Cushion et al, , 2012Dekavalla, 2012). Dekavalla (2012), for example, found Scottish newspapers were far more informative than their English counterparts during the 2001 and 2005 general election campaigns.…”
Section: Content Analysis Democracy Interviews Politics/political mentioning
confidence: 99%
See 2 more Smart Citations